Review of the Issues and Governance of Genetically Modified Organism in Malaysia - Hafis Aliaziz, Mohamad; Ab Rahma, Suhaimi (International Journal of Engineering and Technology, 2018)
This paper discusses the issues of modern practice of biotechnology in Malaysia. As a developing country, Malaysia is putting a lot of effort on the development of biotechnology which is targeted to be a new economic engine for the country. Although the modern biotechnology with the focus in producing genetically modified products seems to give many benefits, but it has raised concerns on several issues arising out of the use of the modified organisms.Â  Thus, a good governance of GMO is required to control the issues so that it can reduce the concerns over safety and halal issues. It is suggested that although the government has introduced laws that govern the practice of biotechnology, it still requires improvement so it can provide overall control to the practice of modern biotechnology in Malaysia.Â Â
Keywords: Genetically Modified Organism; Biotechnology